Identification of Two Major QTLs in Brassica napus Lines With Introgressed Clubroot Resistance From Turnip Cultivar ECD01 - Yu, Fengqun; Zhang, Yan; Wang, Jinghe; Chen, Qilin; Karim, Md. Masud; Gossen, Bruce D.; Peng, Gary (Frontiers in Plant Science, 2022)
Plasmodiophora brassicae causes clubroot disease in brassica crops worldwide. Brassica rapa, a progenitor of Brassica napus (canola), possesses important sources for resistance to clubroot. A doubled haploid (DH) population consisting of 84 DH lines were developed from a Backcross2 (BC2) plant through an interspecific cross of B. rapa turnip cv. ECD01 (resistant, R) with canola line DH16516 (susceptible, S) and then backcrossed with DH16516 as the recurrent parent. The DH lines and their parental lines were tested for resistance to four major pathotypes (3A, 3D, 3H, and 5X) of P. brassicae identified from canola. The R:S segregation ratio for pathotype 3A was 1:3, and 3:1 for pathotypes 3D, 3H, and 5X. From genotyping by sequencing (GBS), a total of 355.3 M short reads were obtained from the 84 DH lines, ranging from 0.81 to 11.67 M sequences per line. The short reads were aligned into the A-genome of B. napus “Darmor-bzh” version 4.1 with a total of 260 non-redundant single-nucleotide polymorphism (SNP) sites. Two quantitative trait loci (QTLs), Rcr10ECD01 and Rcr9ECD01, were detected for the pathotypes in chromosomes A03 and A08, respectively. Rcr10ECD01 and Rcr9ECD01 were responsible for resistance to 3A, 3D, and 3H, while only one QTL, Rcr9ECD01, was responsible for resistance to pathotype 5X. The logarithm of the odds (LOD) values, phenotypic variation explained (PVE), additive (Add) values, and confidence interval (CI) from the estimated QTL position varied with QTL, with a range of 5.2–12.2 for LOD, 16.2–43.3% for PVE, 14.3–25.4 for Add, and 1.5–12.0 cM for CI. The presence of the QTLs on the chromosomes was confirmed through the identification of the percentage of polymorphic variants using bulked-segregant analysis. There was one gene encoding a disease resistance protein and 24 genes encoding proteins with function related to plant defense response in the Rcr10ECD01 target region. In the Rcr9ECD01 region, two genes encoded disease resistance proteins and 10 genes encoded with defense-related function. The target regions for Rcr10ECD01 and Rcr9ECD01 in B. napus were homologous to the 11.0–16.0 Mb interval of chromosome A03 and the 12.0–14.5 Mb interval of A08 in B. rapa “Chiifu” reference genome, respectively.